Time-based competition is not enough - Hout, Thomas M.
Thomas M. Hout reports how Toyota, Chrysler and AT&T are experimenting with new ways of managing the conflicting priorities facing R&D leaders today.
Companies willing to embrace complexity are screening managers for a different, bigger set of personal attributes.
Heads of R&D in large corporations are everyday faced with managing conflicting priorities-on the one hand, training their people in disciplines and creating new technology and, on the other; developing rapidly a stream of new products for customers. These priorities not only compete for resources but also suggest different organizational structures, timelines, management metrics, and managers best suited to lead them. Some companies have been experiencing with new ways to manage these conflicting priorities and organizational requirements by asking managers to play new roles, by creating new organizational shapes and styles, by physically housing R&D people differently, and by selecting different, non-obvious people for senior jobs in R&D. These experiments have helped these companies accomplish both sets of priorities with less compromise or interference.